Clinical, dietary and demographic characteristics interfering on quality of life of cancer patients - Duarte Bonini Campos, Juliana Alvares [UNESP]; Silva, Wanderson Roberto da [UNESP]; Bernardes Spexoto, Maria Claudia [UNESP]; Serrano, Sergio Vicente; Maroco, Joao (Inst Israelita Ensino & Pesquisa Albert Einstein, 2018)
Objective: To estimate the dietary intake of cancer patients and its relation with clinical and demographic characteristics, and to assess the contribution of dietary intake, appetite/symptoms and clinical and demographic characteristics to their quality of life. Methods: The consumption of energy and macronutrients of patients was estimated. The relation between dietary intake and clinical and demographic characteristics was evaluated by analysis of variance. The intake of energy and macronutrient of the patients was compared to the nutritional recommendations using 95% confidence interval. The Cancer Appetite and Symptom Questionnaire (CASQ) and the European Organization for Research and Treatment of Cancer (EORTC QLQ C-30) were used to assess appetite/symptoms and quality of life, respectively. The psychometric properties of the instruments were estimated. A structural equation model was prepared. Results: In this study, 772 cancer patients (63.1% women) participated. There was a significant relation between dietary intake and work activity, economic class, specialty field of cancer, type of treatment and nutritional status. Patients' energy and macronutrients intake was below recommended values. Both CASQ and EORTC 0111 C-30 were refined to fit the data. In the structural model, impaired appetite, more symptoms, presence of metastasis, being female and of higher economic classes were characteristics that significantly contributed to interfering in patients' quality of life. Conclusion: The dietary intake of oncology patients did not reach the recommended values. Different characteristics impacted on quality of life of patients and should be considered in clinical and epidemiological protocols.
Keywords: Dietetics; Eating; Neoplasms; Quality of life